Biliary atresia: a review - Palacios-Rodríguez, Patricia M.; Granados-Romero, Juan José; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Mendizabal-Velazquez, Alondra; González-Martínez, Itaty C.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Bile duct atresia (BA) is a severe, progressive cholangiopathy characterized by fibrous and inflammatory obliteration of the intrahepatic and extrahepatic bile ducts. It leads to liver failure, scarring, and end-stage cirrhosis if timely treatment is not achieved. It represents the number one indication for pediatric liver transplantation as a single disease worldwide. Various etiological factors have been associated with BA, such as structural malformations, viral, immune-mediated, and genetic infections. The incidence of BA varies around the world. Untreated BA patients have a 2-year mortality of nearly 100%. The clinical picture is characterized by jaundice, acholia, and jaundice that persists beyond the first 2 weeks of life. Direct or conjugated bilirubin remains the primary screening laboratory test for BA; elevated values ​​occur within the first 2 days of life. Currently, the primary treatment of choice is the Kasai portoenterostomy; the success of surgery has been based on the restoration of bile flow and the elimination of jaundice. However, more than 70% of patients develop liver cirrhosis secondary to persistent liver inflammation, which will require liver transplantation. The following review of the literature aims to collect relevant information from what has been published in recent years on bile duct atresia; focused on the study of etiology, pathophysiology, advances in genetics and immunology. As well as the results associated with surgical treatment and the requirement for liver transplantation.